O Brasil e a cadeia automobilística: Uma avaliaç\~ao das políticas públicas para maior produtividade e integraç\~ao internacional entre os anos 1990 e 2014 - Uallace Moreira Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– From the 1990s, it intensified in the global economy the implementation of strategies for companies of fragmenting their production processes and allocate their productive activities in various countries and regions, forming with this global value chains to recreate the international division of work in the global economy. Given this scenario, sectoral policies were implemented as the Brazilian Automotive Regime (RAB) in 1996 and the Innovate-Auto in 2012 to promote the automotive sector gain in competitiveness and productivity. The objective of this study is to analyze these policies for the automotive industry adopted from the 1990s and its impact on Brazil's participation in the automotive supply chain, as well as its relation to the dynamics of the Brazilian international insertion in recent decades, proposing further ideas contribute to the reflection on the construction of a public policy agenda in Brazil that aims to integrate the country in the global chain of automotive value.
Keywords: F02; F15; L62; L00; L2; O3; O21; O22; 330; global values chains; automobile industry; Brazilian automotive regime (bar); innovation-auto